Keteladanan Kepemimpinan Kharismatik Kepala Madrasah Dalam Membangun Kerakter Peserta Didik Di MTs Azzainiyyah Kabupaten Sukabumi - Khoirunnisa Nurfadilah; Mulyawan Safwandy Nugraha (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
. Character is a value related to a person's personality, based on religious, socio-cultural, and customary norms. A strong nation is a nation of good character and personality. A character is a real portrait of a person. Everyone's character is different and becomes a good and bad picture of someone, especially the character of a student in the school environment. Character education must continue to be developed in schools and refer to the example of the leaders of school institutions or madrasahs. The head of the madrasah is an example for school residents, especially students, therefore the leadership of the head of the madrasah must be able to set an example to be emulated by educators and students. The purpose of this study is to provide an overview of charismatic leadership examples to build the character of students in MTs Azzainiyyah Sukabumi Regency. The research approach uses qualitative with a descriptive type. The research instrument is the researcher himself. Data collection through interviews, observation and documentation. This research shows that charismatic leadership can shape the character of students. All efforts to increase the value of charismatic leadership will improve the character of students.